Serum Reduced Culture of Tuna Fish Cells - Karimy, Kourosh. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Committee: David Kaplan, Qiaobing Xu, and Reza Ovissipour.; Keyword: Bioengineering.